Kingdom of Lesotho : Technical Assistance Report-Implementation of Basel II. (IMF Staff Country Reports; Country Report ;, 2020)
This mission, a follow up to the earlier mission from IMF AFRITAC South (AFS) conducted in March 2017 (STX Mr. Bernie Egan), was designed to further help the authorities in the implementation of Basel II and select elements of Basel III. The main objectives of the mission were to help the CBL finalize the Draft Guidelines to banks on Pillar 1; assist in the implementation of Pillar 2, with attention paid to the Supervisory Review and Evaluation Process (SREP) and the bankso Internal Capital Adequacy Assessment Process (ICAAP); and evaluate current disclosure requirements in view of the recent revision of Pillar 3 by the Basel Committee on Banking Supervision (BCBS). The adoption of select elements of Basel III especially those related to definition of capital was discussed.